An analysis of factors that influence patient preference of third‐line therapy for overactive bladder. Issue 8 (14th September 2022) - Kapur, Anjali; Harandi, Arshia Aalami; Cohen, Tal; Ruan, Heng; Dabrowski, Colin; Anderson, Rebecca; Hwang, Kuemin; Lee, Edwin; Weissbart, Steven; Kim, Jason
Abstract: Objective: Patients with overactive bladder (OAB) refractory to first‐ and second‐line therapy may pursue third‐line therapies, including intradetrusor onabotulinum toxin‐A (BTX), peripheral tibial nerve stimulation (PTNS), and sacral neuromodulation (SNM). The factors that influence patient preference for each treatment modality have not yet been explored. This study sought to investigate the specific parameters that patients consider in choosing a third‐line therapy for OAB. Methods: Patients refractory to first‐ and second‐line therapies for OAB were identified in our outpatient clinic and asked to watch an educational video providing information on the risks and benefits of each third‐line treatment option. They were then given a questionnaire to rank their preference of therapy and select reasons for why they found each therapy favorable and unfavorable. Patients under age 18 years, non‐English speakers, those with a developmental disability, and those with a diagnosis of neurogenic bladder were excluded. Results: Of the 98 patients included in the study, 40 participants (40.8%) chose intradetrusor BTX injections, 34 (34.7%) chose PTNS, and 16 (16.3%) chose SNM as their first choice. Seven patients (7.1%) chose none of the offered therapies, and one patient (1.0%) chose all three therapies with equal preference. BTX was found most attractive for its long efficacy (47%); its least attractive feature was the potential need for self‐catheterization due to urinary retention (54%). PTNS was found most attractive for being a nonsurgical option (32%) and having no reported significant complications (39%); its least attractive feature was need for frequent office visits (61%). SNM was found most attractive for its potential for long‐term relief without frequent office visits (53%); its least attractive feature was need for an implanted device (33%). Patients opting for SNM had higher scores on Urinary Distress Inventory‐6 and Incontinence Impact Questionnaire‐7 questionnaires when compared to patients opting for BTX injections or PTNS ( p < 0.05). 47.4% of patients eventually pursued a third‐line therapy. Of those, there was a 67.6% concordance rate between the therapy patients ranked first and the therapy they eventually underwent. Conclusions: Patients with more severe OAB symptoms opt for more invasive and less time‐consuming therapy with the potential for long‐term relief, namely SNM. Despite thorough counseling, many patients do not progress to advanced OAB therapies. Understanding factors that influence patients' affinity toward a specific type of treatment can aid with individualized counseling on third‐line OAB therapies.